Acoustically-Stimulated Nanobubbles: Opportunities in Medical Ultrasound Imaging and Therapy - Helfield, Brandon; Zou, Yiran; Matsuura, Naomi (Frontiers in Physics, 2021)
Medical ultrasound is one of the most widely used imaging modalities worldwide. Microbubbles, typically ~1 - 8 µm in diameter, are ultrasound contrast agents confined to the vasculature due to their size. Microbubbles have broadened the scope of medical ultrasound, permitting real-time imaging of the microvasculature for blood flow assessment, molecular imaging, and even non-invasive site-specific therapy. Recently, there has been increasing interest in developing submicron, ‘nanoscale’ agents to extend the utility of medical ultrasound. In this review, we discuss the development of lipid-encapsulated, acoustically responsive, nanobubbles (~200 - 800 nm in diameter), a next-generation ultrasound contrast agent. First, medical ultrasound and bubble-based contrast agents are introduced, followed by the advantages of scaling down bubble size from an acoustic and biological viewpoint. Next, we present how lipid-encapsulated nanobubbles can be developed towards meeting clinically meaningful endpoints, from agent synthesis and characterization to in vivo considerations. Finally, future opportunities of nanobubbles for advanced applications in ultrasound diagnostic and therapeutic medicine are proposed.